Boosting the activity of catalytic oxidation of 5-hydroxymethylfurfural to 2, 5-diformylfuran over nitrogen-doped manganese oxide catalysts. Issue 16 (31st May 2019) - Ke, Qingping; Jin, Yangxin; Ruan, Fei; Ha, Minh Ngoc; Li, Dandan; Cui, Peixin; Cao, Yali; Wang, Hao; Wang, Tongtong; Nguyen, Van Noi; Han, Xinya; Wang, Xi; et al.
Abstract : Doping of nitrogen into MnO2 is employed as an efficient catalyst for the catalytic oxidation of HMF to DFF under an oxygen atmosphere. Abstract : Approaches for the catalytic oxidation of biomass-based 5-hydroxymethylfurfural (HMF) into valuable chemicals are in great demand; however, their development is still challenging. Herein, we present nitrogen-doped manganese oxide (N-MnO2 ) catalysts that possess extraordinary catalytic performance (a >99.9% 2, 5-diformylfuran selectivity, a 100% HMF conversion, and decent reusability) at room temperature without any additives. Structural changes, i.e. slight elongation of the Mn–O bonds and reduction of the coordination number of Mn sites, occur after doping of nitrogen into MnO2, as confirmed via characterization by extended X-ray absorption fine structure (EXAFS), H2 -temperature programmed reduction (H2 -TPR) and X-ray photoelectron spectroscopy (XPS). Mechanistic studies indicate that surface defect sites and coordinatively unsaturated Mn sites induced by nitrogen doping play a key role in promoting the oxidative activity.